Law and development and the global discourses of legal transfers - Nicholson, Penelope; Gillespie, John (John Stanley) (Cambridge Cambridge University Press, 2012)
This volume of essays contributes to the understanding of global law reform by questioning the assumption in law and development theory that laws fail to transfer because of shortcomings in project design and implementation. It brings together leading scholars who demonstrate that a synthesis of law and development, comparative law and regulatory perspectives (disciplines which to date have remained intellectually isolated from each other) can produce a more nuanced understanding about development failures. Arguing for a refocusing of the analysis onto the social demand for legal transfers, and drawing on empirically rich case studies, contributors explore what recipients in developing countries think about global legal reforms. This analytical focus generates insights into how key actors in developing countries understand global law reforms and how to better predict how legal reforms are likely to play out in recipient countries"--
Machine generated contents note: 1. Interpreting legal transfers: the implications for law and development John Gillespie and Pip Nicholson; Part I. Theorising Legal Transfers Towards an Interpretative Analysis: 2. Relocating global legal scripts in local networks of meaning John Gillespie; 3. International and domestic selective adaptation: the case of Charter 08 Pitman Potter; 4. Rights and regulation as a framework for exploring reverse legal transfers: hegemony and counter-hegemony in the Bolivian water sector Bronwen Morgan; Part II. Re-interpreting Universalised Standards of Practice: TRIPS and Human Rights Norms: 5. The transfer of pharmaceutical patent laws: the case of India's Paragraph 3(d) Christopher Arup; 6. Between rhetoric and reality: the use of international human rights norms in law reform debates in China Sarah Biddulph; Part III. Re-interpreting the Rule of Law as Transfer: 7. Between global norms and domestic realities: judicial reforms in China Randall Peerenboom; 8. Official discourses and court-oriented legal reform in Vietnam Pip Nicholson and Simon Pitt; 9. Constructing law from development: cause lawyers, generational narratives, and the rule of law in Thailand Frank Munger; Part IV. Re-interpreting Global Family and Religious Norms: 10. Family law transfers from Europe to Africa: lessons for the methodology of comparative legal research Mark Van Hoecke; 11. Resistible force meets malleable object: the story of the 'introduction' of norms of gender equality into Japanese employment practice Frank Upham; 12. Discordant voices on the status of Islam under the Malaysian constitution Elsa Satkunasingam; 13. Unpacking a global norm in a local context: an historical overview of the epistemic communities that are shaping Zakat practice in Malaysia Kerstin Steiner.
Includes bibliographical references and index.
Keywords: Law and economic development. -- Electronic book; LAW / Comparative